Mechanothermodynamics - Sosnovskiy, Leonid; Sherbakov, Sergei; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph addresses the foundations of mechanothermodynamics and analyzes two of its key principles-damage of everything that exists has no conceivable limits, and effective energy (entropy) flows caused by loads of a different nature do not have a cumulative property; they interact dialectically. The authors examine a generalized model of energy and entropy states of a mechanothermodynamical medium, which generally is a continuum (liquid, gaseous) containing distributed solid deformable, and, therefore, damageable bodies, as a problem of information states of movable and damageable systems and express a solution in the first approximation. The book goes on to analyze some directions of further research in its conclusion. It is ideal for scientists, engineers, post graduate and master students of mechanics, mathematics and physics.
Introduction -- Energy States of the Mechanothermodynamic System  and the Analysis of its Damageability -- Entropy States of Mechanothermodynamic Systems and their Evolution -- Principles of Mechanothermodynamics -- Generalized Model of Mechanothermodynamic States of Continuum -- Some Areas of Further Research.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Materials -- Analysis; Materials; Engineering Thermodynamics, Heat and Mass Transfer; Characterization and Analytical Technique; Materials Engineering; Thermodynamics